Humanized three-dimensional scaffold xenotransplantation models for myelodysplastic syndromes - Altrock, Eva; Sens-Albert, Carla; Jann, Johann-Christoph; Flach, Johanna; Riabov, Vladimir; Schmitt, Nanni; Xu, Qingyu; Mehralivand, Arwin; Hecht, Anna; Steiner, Laurenz; Streuer, Alexander; Nowak, Verena; et al. (Experimental hematology, 2022)
Patient-derived xenograft (PDX) models have emerged as versatile preclinical platforms for investigation of functional pathomechanisms in myelodysplastic syndromes (MDS) and other myeloid neoplasms. However, despite increasingly improved methodology, engraftment efficiencies frequently remain low. Humanized three-dimensional scaffold models (ossicle xenotransplantation models) in immunocompromised mice have recently been found to enable improved engraftment rates of healthy and malignant human hematopoiesis. We therefore interrogated the feasibility of using four different three-dimensional ossicle-based PDX models for application with primary MDS samples. In a fully standardized comparison, we evaluated scaffold materials such as Gelfoam, extracellular matrix (ECM), and human or xenogenous bone substance in comparison to intrafemoral (IF) co-injection of bone marrow (BM)-derived mesenchymal stromal cells (MSCs) and CD34+ hematopoietic stem and progenitor cells (HSPCs). Our study included13 primary MDS patient samples transplanted in parallel according to these five different conditions. Engraftment of MDS samples was assessed by flow cytometry, immunohistological staining, and molecular validation. We determined that three-dimensional ossicle-based methods achieved higher relative rates of engraftment and enabled long-term retrievability of patient-derived MSCs from implanted ossicles. In summary, HSPCs and MSCs derived from MDS BM, which did not significantly engraft in NSG mice after intrafemoral injection, were able to colonize humanized scaffold models. Therefore, these models are promising new xenotransplantation techniques for addressing preclinical and functional questions of the interaction between hematopoiesis and the BM niche in MDS.